Primary angiitis of the central nervous system: diagnosis and treatment. (5th July 2018) - Beuker, Carolin; Schmidt, Antje; Strunk, Daniel; Sporns, Peter B.; Wiendl, Heinz; Meuth, Sven G.; Minnerup, Jens
Primary angiitis of the central nervous system (PACNS) represents a rare inflammatory disease affecting the brain and spinal cord. Stroke, encephalopathy, headache and seizures are major clinical manifestations. The diagnosis of PACNS is based on the combination of clinical presentation, imaging findings (magnetic resonance imaging and angiography), brain biopsy, and laboratory and cerebral spinal fluid (CSF) values. PACNS can either be confirmed by magnetic resonance angiography (MRA)/conventional angiography or tissue biopsy showing the presence of typical histopathological patterns. Identification of PACNS mimics is often challenging in clinical practice, but crucial to avoid far-reaching treatment decisions. In view of the severity of the disease, with considerable morbidity and mortality, early recognition and treatment initiation is necessary. Due to the rareness and heterogeneity of the disease, there is a lack of randomized data on treatment strategies. Retrospective studies suggest the combined administration of cyclophosphamide and glucocorticoids as induction therapy. Immunosuppressants such as azathioprine, methotrexate or mycophenolate mofetil are often applied for maintenance therapy. In addition, the beneficial effects of two biological agents (anti-CD20 monoclonal antibody rituximab and tumour necrosis factor-α blocker) have been reported. Nevertheless, diagnosis and treatment is still a clinical challenge, and further insights into the immunopathogenesis of PACNS are required to improve the diagnosis and management of patients. The present review provides a comprehensive overview of diagnostics, differential diagnoses, and therapeutic approaches of adult PACNS.